2022
DOI: 10.7494/geom.2022.16.2.95
|View full text |Cite
|
Sign up to set email alerts
|

An Estimation of Soil Erosion Rate Hot Spots by Integrated USLE and GIS Methods: a Case Study of the Ghiss Dam and Basin in Northeastern Morocco

Abstract: Soil erosion is a major factor leading to dams’ siltation and reducing their storage capacity. This study mapped the hot spots of soil erosion areas to predict the soil erosion/siltation in the Ghiss basin/dam (northeastern Morocco). In this context, various data has been prepared in the geographical information system for the estimation of soil erosion by integrating the universal soil loss equation (USLE). The result of this study revealed that soil loss rate ranges between0 and 19 t∙ha−1∙yr−1. Therefore, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…The characteristic lithology of this watershed might be another reason [97]. In addition, inappropriate agriculture practices and overgrazing also acted as other driving forces in gully erosion in this study area [62].…”
Section: Identification Of Gully Zonesmentioning
confidence: 83%
See 1 more Smart Citation
“…The characteristic lithology of this watershed might be another reason [97]. In addition, inappropriate agriculture practices and overgrazing also acted as other driving forces in gully erosion in this study area [62].…”
Section: Identification Of Gully Zonesmentioning
confidence: 83%
“…However, insufficient and poor sanitation facilities, as well as unsustainable agriculture in the study area, have resulted in deterioration of groundwater quality in this region [60,61]. Previously, a study [62] using the RUSLE method reported that more than 50% of the watershed is considered as moderately eroded. Thus, our research effort is directed towards a deep understanding of gully erosion in this study area.…”
Section: Study Areamentioning
confidence: 98%
“…Whether in agriculture, energy production or manufacturing, poor water quality can compromise the quality of end products, affect production costs and cause long-term environmental damage [16,17]. Faced with the multiple challenges posed by water quality management, it is imperative to have reliable and effective methods for its assessment [18][19][20][21]. This is where Water Quality Indices (WQIs) come into their own.…”
Section: Introductionmentioning
confidence: 99%
“…The Ghiss-Nekor aquifer serves as the primary groundwater storage in the Al-Hoceima province, a semi-arid Mediterranean area plagued by elevated groundwater salinity. This issue complicates drinking water supply management, worsened by reduced regulation capacity of the prinipal dam in the area (MBAK dam) as a result of silt accumulation [7]. Understanding the origins of salinization in this area is pivotal for managing the region's drinking water resources effectively.…”
Section: Introductionmentioning
confidence: 99%